C80-grade concrete with improved low-temperature toughness and preparation method thereof
By using air-induced polycarboxylic acid water reducer and end-carboxylic polybutadiene liquid rubber coated inorganic filler toughening agent in high-strength concrete, the problem of high-strength concrete being prone to cracks in low-temperature environments is solved, and its low-temperature toughness is significantly improved, ensuring its stable application in cold areas.
Patent Information
- Application Number
- CN202510280665.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-11
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-03-11
AI Technical Summary
High-strength concrete is prone to cracks in low-temperature environments, and its low-temperature toughness is not enough to support long-term application in cold areas.
The gas-induced polycarboxylic acid water reducing agent prepared by copolymerizing alkenyl polyether large monomers, monoalkenyl polyols, monoalkenyl acid compounds, and alkenyl aromatic compounds is used to improve their ability to generate new interfaces by controlling the relative proportion of monoalkenyl polyols and alkenyl aromatic compounds, and introduce tiny, uniform and stable bubbles to adjust the pore structure of the concrete; at the same time, end carboxylic polybutadiene liquid rubber is used to coat the inorganic filler toughener to absorb external forces and temperature changes and avoid crack expansion.
It significantly improves the low-temperature toughness of concrete, avoids the rapid expansion of cracks, and does not reduce the compressive strength, expanding the application range of high-strength concrete in different climatic regions.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete, and in particular relates to C80 grade concrete with improved low-temperature toughness and a preparation method thereof. Background Art
[0002] With the continuous development of the construction industry, modern engineering structures are developing towards large spans, super high-rises, and heavy loads. At the same time, special engineering fields such as marine engineering and nuclear power engineering are also emerging. These projects have put forward more stringent requirements on the performance of concrete, and high-strength concrete has emerged and has been widely studied and applied.
[0003] Due to its high strength, high-strength concrete can effectively reduce the size of structural components, thereby increasing the usable space of the building, reducing the deadweight of the structure, and improving the stability of the foundation. Improving the strength of concrete is mainly achieved by increasing the amount of cementitious materials and reducing the water-binder ratio. However, a low water-binder ratio will cause the hydration heat of concrete to be concentrated in the early stage, and at this time, the tensile strength and ultimate tensile strain of the concrete are relatively low, which is easy to cause early shrinkage microcracks and segregation cracks in the concrete, such as the high-performance C80 concrete water reducer disclosed in patent CN103922637B, and its preparation method and use method.
[0004] Studies have shown that adding an appropriate amount of mineral admixtures can make concrete more compact, improve the interface transition zone, and reduce the hydration heat, which can overcome the problem of many early cracks and poor toughness of high-strength concrete. However, its toughness is still not enough to support this kind of high-strength concrete to work in cold and extremely cold areas for a long time. Under low temperature and impact load, the interface transition zone is a weak link for crack expansion, and the interface transition zone between aggregate and cement stone is still easily damaged, such as the patent CN111454033B disclosed A C80 ultra-high pumping concrete and a preparation method thereof, comprising the following raw materials in parts by weight: 270-310 parts of cement; 690-720 parts of sand; 950-990 parts of crushed stone; 240-260 parts of mineral admixture; 8.5-10.5 parts of polycarboxylic acid water reducer; 25-56 parts of graphite powder; 10-20 parts of coal gangue ultra-fine powder; 0.0145-0.145 parts of air entraining agent; 2.4-2.6 parts of activator; and 135-147 parts of water.
[0005] Therefore, it is necessary to further improve the low-temperature toughness of high-strength concrete using mineral admixtures in order to expand the application of high-strength concrete in different climatic regions. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a C80 grade concrete with improved low-temperature toughness and a preparation method thereof, comprising an air-entraining polycarboxylate water-reducing agent prepared by copolymerization of alkenyl polyether macromonomers, monoalkenyl polyols, monoalkenyl acid compounds, and alkenyl aromatic compounds. By controlling the relative proportions of monoalkenyl polyols with strong hydrophilicity and lipophilic alkenyl aromatic compounds in the air-entraining polycarboxylate water-reducing agent, its ability to generate new interfaces is improved, a large number of tiny, uniform and stable bubbles are introduced during the concrete mixing process, the pore structure of the concrete is adjusted, and the low-temperature toughness is improved; in addition, the toughening agent is an inorganic filler coated with a terminal carboxyl polybutadiene liquid rubber that can produce elastic deformation. When the concrete is subjected to external force or temperature changes, the toughening agent can absorb part of the energy to avoid the rapid expansion of cracks, thereby synergistically improving the toughness of the concrete.
[0007] In order to achieve the above objectives, the following technical solutions are adopted: A C80 grade concrete with improved low-temperature toughness comprises the following raw materials: 330-380 parts by weight of cement, 100-150 parts by weight of admixture, 600-700 parts by weight of fine aggregate, 850-1000 parts by weight of coarse aggregate, 7-10 parts by weight of air-entraining polycarboxylate water-reducing agent, 25-35 parts by weight of toughening agent and water, wherein the mass ratio of the total mass of cement and admixture to water is 1:0.2-0.28; the air-entraining polycarboxylate water-reducing agent is copolymerized by alkenyl polyether macromonomer, monoalkenyl polyol, monoalkenyl acid compound and alkenyl aromatic hydrocarbon compound in a mass ratio of 100:10-20:5-10:5-10, the monoalkenyl polyol is prepared by reacting glycidyl acrylate compound and monoamino polyol compound in a molar ratio of epoxy group to amino group of 1:1.0-1.05; the toughening agent is an inorganic filler coated with carboxyl-terminated polybutadiene liquid rubber.
[0008] The glycidyl acrylate compound is selected from one or a combination of glycidyl acrylate and glycidyl methacrylate; the monoamino polyol compound is selected from one or a combination of two or more of tromethamine, 3-amino-1,2-propanediol, 2-aminobutane-1,3-diol, 2-(aminomethyl)-1,3-propanediol, 2-amino-2-methyl-1,3-propanediol, and 2-amino-2-ethyl-1,3-propanediol; preferably tromethamine.
[0009] The air-entraining polycarboxylate water-reducing agent is prepared by a method comprising the following steps: 1) Under an inert atmosphere, a glycidyl acrylate compound and a monoamino polyol compound are dissolved in an organic solvent, and the temperature is controlled to react. After the reaction is completed, the organic solvent is removed by distillation, and the monoolefin polyol is separated by column chromatography to obtain a monoolefin polyol; 2) Under an inert atmosphere, add alkenyl polyether macromonomer, monoalkenyl polyol, monoalkenyl acid compound, alkenyl aromatic compound, initiator and chain transfer agent into a reaction kettle and mix evenly, raise the temperature to react, lower the temperature after the reaction, add water to adjust the solid content, and adjust the pH to obtain an air-entraining polycarboxylic acid water-reducing agent.
[0010] In step 1), the organic solvent is selected from one or a combination of two or more of methanol, ethanol, and isopropanol. The temperature control is to control the temperature to 25-50°C. The reaction time is 24-48h. The eluent for column chromatography is a mixture of chloroform and methanol in a volume ratio of 1:1-10.
[0011] In step 2), the alkenyl aromatic compound is selected from one or a combination of two or more of styrene, allylbenzene and 3-methylstyrene.
[0012] The number average molecular weight of the alkenyl polyether macromonomer is 1000-1500, and the macromonomer is selected from one or a combination of two or more of isopentenyl polyoxyethylene ether, methyl allyl polyoxyethylene ether, ethylene glycol monovinyl polyethylene glycol ether, and allyl polyoxyethylene ether.
[0013] The monoolefinic acid compound is selected from one or a combination of two or more of acrylic acid, methacrylic acid, maleic acid, fumaric acid, itaconic acid, sodium allyl sulfonate, sodium methallyl sulfonate, sodium vinyl sulfonate, sodium allyl sulfonate, sodium methallyl sulfonate, sodium styrene sulfonate, sodium p-styrene sulfonate, and 2-acrylamido-2-methylpropane sulfonic acid.
[0014] In step 2), the initiator is selected from one or a combination of two or more of BPO, isophenyl hydroperoxide, and tert-butyl hydroperoxide; the amount of the initiator is 1-3wt% of the mass sum of alkenyl polyether macromonomer, monoalkenyl polyol, monoalkenyl acid compound, and alkenyl aromatic hydrocarbon compound. The chain transfer agent is selected from one or a combination of mercaptoethanol and dodecyl mercaptan. The amount of the chain transfer agent is 0.5-0.8wt% of the mass sum of alkenyl polyether macromonomer, monoalkenyl polyol, monoalkenyl acid compound, and alkenyl aromatic hydrocarbon compound. The temperature is raised to 60-80°C, and the reaction time is 3-5h. The pH is adjusted to 7-9 with alkali solution, and the alkali solution is selected from one or a combination of two or more of sodium hydroxide solution, sodium carbonate solution, and sodium bicarbonate solution. The solid content is adjusted to 35-45wt% by adding water.
[0015] Air-entraining polycarboxylate water-reducing agent can introduce a large number of tiny, uniform and stable bubbles during the concrete mixing process, but a large number of small bubbles will merge or break, forming weak points that reduce the compressive strength of concrete. The use of terminal carboxyl polybutadiene liquid rubber-coated inorganic filler toughening agent can cooperate with air-entraining polycarboxylate water-reducing agent to improve the low-temperature toughness of concrete without reducing the compressive strength.
[0016] The toughening agent is a carboxyl-terminated polybutadiene liquid rubber coated inorganic filler, which is prepared by a method comprising the following steps: Inorganic filler, carboxyl-terminated polybutadiene liquid rubber, organic solvent and ball milling medium are added into a ball mill, ball milling is performed to obtain ball milling slurry, and the toughening agent is obtained by filtering and drying.
[0017] The ball milling medium is zirconium oxide beads with a particle size of 0.1mm-0.5mm. The rotation speed of the ball mill is 200-800r / min. The ball milling time is 3-5h. The mass ratio of the inorganic filler and the carboxyl-terminated polybutadiene liquid rubber to the ball milling medium is 1:20-25. The mass ratio of the inorganic filler, the carboxyl-terminated polybutadiene liquid rubber, and the organic solvent is 5:0.4-0.5:10-15. The organic solvent is selected from one or a combination of two or more of toluene, benzene, dichloromethane, methyl ethyl ketone, and ethyl acetate. The ball milling temperature is 25-50°C. The drying is drying at 60-80°C and a vacuum degree of 0.01-0.1MPa for 1-3h.
[0018] The number average molecular weight of the carboxyl-terminated polybutadiene liquid rubber is 3000-5000.
[0019] The inorganic filler has an average particle size of 50-100 nm and is selected from one or a combination of two or more of silicon dioxide, calcium carbonate, talcum powder and magnesium carbonate.
[0020] The admixture is selected from fly ash, mineral powder or a combination of the two.
[0021] The admixture is a mixture of fly ash and mineral powder in a mass ratio of 1:2-5.
[0022] The fly ash is selected from one of Class I fly ash and Class II fly ash, or a combination of the two.
[0023] The mineral powder is selected from one of S105 grade mineral powder, S95 grade mineral powder, S75 grade mineral powder or a combination of two thereof.
[0024] The cement is silicate cement with a strength grade of 42.5 to 52.5.
[0025] The fine aggregate is quartz sand with a fineness modulus of 3.0-2.3.
[0026] The coarse aggregate is continuously graded crushed stone with a particle size of 5-20 mm.
[0027] The present invention also provides a method for preparing the above-mentioned C80 grade concrete with improved low-temperature toughness, comprising the following steps: The cement, admixture, air-entraining polycarboxylate water-reducing agent, toughening agent and water are uniformly mixed to obtain slurry, and the coarse aggregate and fine aggregate are added to the slurry and uniformly mixed to obtain C80 grade concrete with improved low-temperature toughness.
[0028] Compared with the prior art, the present invention has the following beneficial effects: The concrete of the present invention comprises an air-entraining polycarboxylate water-reducing agent prepared by copolymerization of alkenyl polyether macromonomer, monoalkenyl polyol, monoalkenyl acid compound and alkenyl aromatic hydrocarbon compound. The relative proportions of monoalkenyl polyol with strong hydrophilic effect and lipophilic alkenyl aromatic hydrocarbon compound in the air-entraining polycarboxylate water-reducing agent are controlled to improve the ability of the air-entraining polycarboxylate water-reducing agent to generate new interfaces. A large number of tiny, uniform and stable bubbles are introduced during the concrete mixing process to adjust the pore structure of the concrete and improve the low-temperature toughness. In addition, the toughening agent is an inorganic filler coated with terminal carboxyl polybutadiene liquid rubber that can generate elastic deformation. When the concrete is subjected to external impact or temperature change, the toughening agent can absorb part of the energy to avoid the rapid expansion of cracks, and has the effect of synergistically improving the toughness of the concrete. DETAILED DESCRIPTION
[0029] The present invention will be further described below in conjunction with specific embodiments, but is not limited to the contents of the specification. Unless otherwise specified, the "parts" described in the embodiments of the present invention are all parts by weight. The reagents used are all commercially available reagents in the art.
[0030] Type I carboxyl-terminated polybutadiene liquid rubber has a number average molecular weight of 5000 and was purchased from Tianyuan Aerospace Materials.
[0031] Type II carboxyl-terminated polybutadiene liquid rubber has a number average molecular weight of 3500 and was purchased from Tianyuan Aerospace Materials.
[0032] Allyl polyoxyethylene ether with a number average molecular weight of APEG1500 was purchased from Wuhan Xinxin Jiali Biotechnology Co., Ltd.
[0033] Continuously graded gravel with a particle size of 5-20 mm was purchased from Huzhou Xinkaiyuan Gravel Co., Ltd.
[0034] Quartz sand with a fineness modulus of 2.6 was purchased from Fengyang Jihui Quartz Sand Co., Ltd.
[0035] Nano-silicon dioxide DK-SiO2-60 with an average particle size of 60 nm was purchased from Zhongke Jinyan (Beijing) Technology Co., Ltd.
[0036] Example 1 1) Under nitrogen atmosphere, 1 mol of glycidyl methacrylate and 1 mol of tromethamine were dissolved in ethanol, and the reaction was carried out at 25°C. After 48 hours of reaction, the ethanol was distilled off and separated by column chromatography on a silica gel column. The eluent was a mixture of chloroform and methanol in a volume ratio of 1:3 to obtain a monoolefin polyol.
[0037] 2) Under nitrogen atmosphere, 100g APEG1500, 20g monoolefin polyol, 10g acrylic acid, 10g styrene, 4.2g BPO and 0.7g mercaptoethanol were added into the reaction kettle and mixed evenly. The mixture was heated to 80°C for reaction for 5h. After the reaction, the mixture was cooled to room temperature. Water was added to adjust the solid content to 45wt%, and the pH was adjusted to 7 with 32wt% sodium hydroxide solution to obtain an air-entraining polycarboxylic acid water reducer.
[0038] 3) Add 50g DK-SiO2-60, 5g type I carboxyl-terminated polybutadiene liquid rubber, 150g toluene, and zirconia beads with a particle size of 0.2mm into a ball mill with a ball-to-material ratio of 20:1. Ball mill at 30℃ for 5h to obtain ball milled slurry, filter it, and dry it at 60℃ and a vacuum degree of 0.08MPa to obtain the toughening agent.
[0039] 4) 330 parts by weight of silicate cement with a strength grade of 52.5, 150 parts by weight of an admixture prepared by mixing grade I fly ash and grade S95 mineral powder in a mass ratio of 1:3, 10 parts by weight of air-entraining polycarboxylic acid water-reducing agent, 35 parts by weight of a toughening agent, and 28 wt% of water accounting for the mass of silicate cement and the admixture are mixed evenly to obtain a slurry; 1000 parts by weight of continuously graded crushed stone and 600 parts by weight of quartz sand with a fineness modulus of 2.6 are added to the slurry and mixed evenly to obtain C80 grade concrete with improved low-temperature toughness.
[0040] Example 2 The rest is the same as Example 1, except that in step 4), the amount of air-entraining polycarboxylate water-reducing agent is 7 parts by mass.
[0041] Example 3 The rest is the same as Example 1, except that in step 2), the amount of monoolefin polyol used is 10 g.
[0042] Example 4 The rest is the same as Example 1, except that in step 2), the amount of styrene used is 5 g.
[0043] Example 5 The rest is the same as Example 1, except that in step 4), the amount of toughening agent used is 25 parts by mass.
[0044] Example 6 The rest is the same as Example 1, except that in step 1), tromethamine is replaced by an equal molar amount of 3-amino-1,2-propanediol.
[0045] Example 7 The rest is the same as Example 1, except that in step 3), the type I carboxyl-terminated polybutadiene liquid rubber is replaced by an equal mass of type II carboxyl-terminated polybutadiene liquid rubber.
[0046] Example 8 1) Under nitrogen atmosphere, 1 mol of glycidyl methacrylate and 1.05 mol of tromethamine were dissolved in ethanol, and the reaction was carried out at 25°C. After 48 hours of reaction, the ethanol was distilled off and separated by column chromatography on a silica gel column. The eluent was a mixture of chloroform and methanol in a volume ratio of 1:3 to obtain a monoolefin polyol.
[0047] 2) Under nitrogen atmosphere, 100g APEG1500, 10g monoolefin polyol, 5g acrylic acid, 10g allylbenzene, 3.75g BPO and 0.625g mercaptoethanol were added into the reaction kettle and mixed evenly. The mixture was heated to 80°C for reaction for 5h. After the reaction, the mixture was cooled to room temperature. Water was added to adjust the solid content to 45wt%, and the pH was adjusted to 7 with 32wt% sodium hydroxide solution to obtain an air-entraining polycarboxylic acid water reducer.
[0048] 3) Add 50g DK-SiO2-60, 4g type I carboxyl-terminated polybutadiene liquid rubber, 100g toluene, and 1080g zirconia beads with a particle size of 0.3mm into a ball mill, and ball mill at 30°C for 5h to obtain a ball-milled slurry, which is then filtered and dried at 60°C and a vacuum degree of 0.08MPa to obtain a toughening agent.
[0049] 4) 380 parts by weight of silicate cement with a strength grade of 52.5, 100 parts by weight of an admixture prepared by mixing grade I fly ash and grade S95 mineral powder in a mass ratio of 1:2, 10 parts by weight of an air-entraining polycarboxylic acid water-reducing agent, 35 parts by weight of a toughening agent, and 28 wt% of water in an amount equal to the mass of the silicate cement and the admixture are mixed evenly to obtain a slurry; 850 parts by weight of continuously graded crushed stone and 700 parts by weight of quartz sand with a fineness modulus of 2.6 are added to the slurry and mixed evenly to obtain C80 grade concrete with improved low-temperature toughness.
[0050] Comparative Example 1 The rest is the same as Example 1, except that in step 2), an equal mass of hydroxyethyl acrylate is used to replace the monoethylenic polyol.
[0051] The concrete prepared in the above examples and comparative examples was subjected to the following performance tests after standard curing for 28 days: Compressive strength and flexural strength: tested in accordance with standard GB / T50081-2002 Test method for mechanical properties of ordinary concrete.
[0052] Low-temperature toughness: Refer to the standard GB / T50082-2009 Test method for long-term performance and durability of ordinary concrete, and perform freeze-thaw cycles (quick freezing method), -20℃ / 2h, 20℃ / 2h, repeated 200 times; after freeze-thaw cycles, heat treatment in a 40℃ oven for 24h, perform flexural strength test again, and calculate the strength loss rate.
[0053] Table 1 Performance test results
[0054] It can be seen from the flexural strength test in Table 1 that the concrete prepared by the present invention has good low-temperature toughness, the air-entraining polycarboxylate water-reducing agent has a greater influence on the room temperature toughness of the concrete, and the toughening agent has a greater influence on the low-temperature toughness of the concrete, and the two have an obvious synergistic effect of improving the toughness.
[0055] It can be seen from the compressive strength performance test results that the toughening agent can improve the toughness of concrete without excessively reducing the compressive strength of the air-entraining water-reducing agent.
[0056] The above detailed description is a specific description of one feasible embodiment of the present invention. The embodiment is not intended to limit the patent scope of the present invention. Any equivalent implementation or modification that does not deviate from the present invention should be included in the scope of the technical solution of the present invention.
Claims
1. A C80 grade concrete with improved low temperature toughness, characterized in that: The invention comprises the following raw materials: 330-380 parts by weight of cement, 100-150 parts by weight of admixture, 600-700 parts by weight of fine aggregate, 850-1000 parts by weight of coarse aggregate, 7-10 parts by weight of air-entraining polycarboxylate water-reducing agent, 25-35 parts by weight of toughening agent and water, wherein the mass ratio of the total mass of cement and admixture to water is 1:0.2-0.28; the air-entraining polycarboxylate water-reducing agent is copolymerized by alkenyl polyether macromonomer, monoalkenyl polyol, monoalkenyl acid compound and alkenyl aromatic hydrocarbon compound in a mass ratio of 100:10-20:5-10:5-10, the monoalkenyl polyol is prepared by reacting glycidyl acrylate compound and monoamino polyol compound in a molar ratio of epoxy group to amino group of 1:1.0-1.05; the toughening agent is an inorganic filler coated with carboxyl-terminated polybutadiene liquid rubber.
2. The C80 grade concrete with improved low temperature toughness according to claim 1, characterized in that: The glycidyl acrylate compound is selected from one or a combination of glycidyl acrylate and glycidyl methacrylate; the monoamino polyol compound is selected from one or a combination of two or more of tromethamine, 3-amino-1,2-propylene glycol, 2-aminobutane-1,3-diol, 2-(aminomethyl)-1,3-propylene glycol, 2-amino-2-methyl-1,3-propylene glycol, and 2-amino-2-ethyl-1,3-propylene glycol.
3. The C80 grade concrete with improved low temperature toughness according to claim 1, characterized in that: The air-entraining polycarboxylate water-reducing agent is prepared by a method comprising the following steps: 1) Under an inert atmosphere, a glycidyl acrylate compound and a monoamino polyol compound are dissolved in an organic solvent, and the temperature is controlled to react. After the reaction is completed, the organic solvent is removed by distillation, and the monoolefin polyol is separated by column chromatography to obtain a monoolefin polyol; 2) Under an inert atmosphere, add alkenyl polyether macromonomer, monoalkenyl polyol, monoalkenyl acid compound, alkenyl aromatic compound, initiator and chain transfer agent into a reaction kettle and mix evenly, raise the temperature to react, lower the temperature after the reaction, add water to adjust the solid content, and adjust the pH to obtain an air-entraining polycarboxylic acid water-reducing agent.
4. The C80 grade concrete with improved low temperature toughness according to claim 3, characterized in that: In step 1), the organic solvent is selected from one or a combination of two or more of methanol, ethanol, and isopropanol; the temperature is controlled at 25-50° C.; and the reaction time is 24-48 hours.
5. The C80 grade concrete with improved low temperature toughness according to claim 3, characterized in that: In step 2), the alkenyl aromatic compound is selected from one or a combination of two or more of styrene, allyl benzene, and 3-methylstyrene; the number average molecular weight of the alkenyl polyether macromonomer is 1000-1500, and is selected from one or a combination of two or more of isopentenyl polyoxyethylene ether, methyl allyl polyoxyethylene ether, ethylene glycol monovinyl polyethylene glycol ether, and allyl polyoxyethylene ether; the monoalkenyl acid compound is selected from one or a combination of two or more of acrylic acid, methacrylic acid, maleic acid, fumaric acid, itaconic acid, sodium allyl sulfonate, sodium methyl allyl sulfonate, sodium vinyl sulfonate, sodium acryl sulfonate, sodium methacrylic sulfonate, sodium styrene sulfonate, sodium p-styrene sulfonate, and 2-acrylamido-2-methylpropane sulfonic acid.
6. The C80 grade concrete with improved low temperature toughness according to claim 1, characterized in that: The toughening agent is a carboxyl-terminated polybutadiene liquid rubber coated inorganic filler, which is prepared by a method comprising the following steps: Inorganic filler, carboxyl-terminated polybutadiene liquid rubber, organic solvent and ball milling medium are added into a ball mill, ball milling is performed to obtain ball milling slurry, and the toughening agent is obtained by filtering and drying.
7. The C80 grade concrete with improved low temperature toughness according to claim 6, characterized in that: The rotation speed of the ball mill is 200-800 r / min; the time of the ball mill is 3-5 hours; the mass ratio of the inorganic filler, the carboxyl-terminated polybutadiene liquid rubber, and the organic solvent is 5:0.4-0.5:10-15.
8. The C80 grade concrete with improved low temperature toughness according to claim 1, characterized in that: The number average molecular weight of the carboxyl-terminated polybutadiene liquid rubber is 3000-5000; the average particle size of the inorganic filler is 50-100 nm, and the filler is selected from one or a combination of two or more of silicon dioxide, calcium carbonate, talc, and magnesium carbonate.
9. The C80 grade concrete with improved low temperature toughness according to claim 1, characterized in that: The admixture is selected from fly ash, mineral powder or a combination of the two; the cement is silicate cement with a strength grade of 42.5 to 52.
5.
10. The method for preparing C80 grade concrete with improved low temperature toughness according to any one of claims 1 to 9, characterized in that: The steps include: The cement, admixture, air-entraining polycarboxylate water-reducing agent, toughening agent and water are uniformly mixed to obtain slurry, and the coarse aggregate and fine aggregate are added to the slurry and uniformly mixed to obtain C80 grade concrete with improved low-temperature toughness.
Citation Information
Patent Citations
Water reducing agent for high-performance c80 concrete and its preparation method and use method
CN103922637B
Method for synthesizing polycarboxylic acid water reducer
CN102336845A
Air entraining type poly carboxylic acid high performance water reducing agent and preparation method thereof
CN102951865A
Shrinkage-reducing poly carboxylic acid water reducing agent and preparation method
CN103193410A
Preparation method of polycarboxylic acid high-performance cement water reducing agent
CN104017139A